2017
DOI: 10.1016/j.techfore.2017.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Openwashing: A decoupling perspective on organizational transparency

Abstract: With the rise of digital technologies, organizations are able to produce, process, and transfer large amounts of information at marginal cost. In recent years, these technological developments together with other macro-phenomena like globalization and rising distrust of institutions has led to unprecedented public expectations regarding organizational transparency. In this study I explore the ways in which organizations resolve the tension between a growing norm to share internal information with the public an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 67 publications
0
43
0
5
Order By: Relevance
“…For example, one way in which such incompletion comes about is when organizations ‘decouple’ (Meyer & Rowan, 1977) their secretive core operations from their outward-facing facade of transparency. In his study on data-centred transparency in local government agencies, Heimstädt (2017) found that city employees facing stakeholder pressure to release their internal data sets to the public, carefully manipulated, curated and remixed data sets in order to protect the underlying processes and services (see also Denis & Goëta, 2017; Kornberger, Meyer, Brandtner, & Höllerer, 2017). Another way in which critical studies explain incomplete accountability is through the mediated nature of transparency.…”
Section: Critical Perspective: Transparency Clouds Accountabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one way in which such incompletion comes about is when organizations ‘decouple’ (Meyer & Rowan, 1977) their secretive core operations from their outward-facing facade of transparency. In his study on data-centred transparency in local government agencies, Heimstädt (2017) found that city employees facing stakeholder pressure to release their internal data sets to the public, carefully manipulated, curated and remixed data sets in order to protect the underlying processes and services (see also Denis & Goëta, 2017; Kornberger, Meyer, Brandtner, & Höllerer, 2017). Another way in which critical studies explain incomplete accountability is through the mediated nature of transparency.…”
Section: Critical Perspective: Transparency Clouds Accountabilitymentioning
confidence: 99%
“…In contrast, research that takes a critical perspective argues that the relation between the two concepts is more complex and that any form of transparency can only ever create incomplete accountability (e.g. Hansen & Flyverbom, 2015;Hansen & Weiskopf, 2019;Heimstädt, 2017;Ringel, 2019). Both perspectives have contributed significantly to our understanding of 'visibility management' (Flyverbom, 2020) in and around organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Our definition of organizational transparency helps us understand the relation between FOI and open data. Open data is a strong form of organizational transparency, as there is relatively little room for the individual employee of an organization to deviate from disclosure programs that are made public (e.g., the code behind the open data portals is oftentimes openly accessible) and sometimes even automated (for an analysis of the residual individual leeway, see Heimstädt ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, data sets previously being used as informal “bargaining chips” between employees within and across public agencies may suddenly become available to everyone (cf. Heimstädt ). Recently, Flyverbom () suggested studying transparency not as a stable order, but as a “form of ordering ” (emphasis added), thereby referring to a processual understanding of these arenas and their politics of disclosure.…”
Section: Theoretical Contextmentioning
confidence: 99%
“…In her seminal essay on the "tyranny of transparency" Marilyn Strathern (2000, p. 310) already asked: "what does visibility conceal?" In my own work (Heimstädt, 2017), I found that even if professionals sympathize with the transparency ideal, doing transparency may result in various forms of decoupling when the ideal clashes with other professional virtues. For the praxis of open strategy, we should therefore not only look to where the light fallsstrategy jams, vlogs and crowdsourcing platformsbut pay attention to forms of opacity and concealment that are enabled by these practices.…”
mentioning
confidence: 94%